2023
DOI: 10.1002/cam4.5594
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies to reverse chemoresistance in colorectal cancer

Abstract: Colorectal cancer (CRC) is a common gastrointestinal malignancy with high morbidity and fatality. Chemotherapy, as traditional therapy for CRC, has exerted well antitumor effect and greatly improved the survival of CRC patients.Nevertheless, chemoresistance is one of the major problems during chemotherapy for CRC and significantly limits the efficacy of the treatment and influences the prognosis of patients. To overcome chemoresistance in CRC, many strategies are being investigated. Here, we review the common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 162 publications
0
19
0
Order By: Relevance
“…In exosomes, encapsulating various biomolecules, including lipids, proteins, coding and non‐coding RNAs, and DNA species, promotes the survival and dissemination of cancer cells against stress, chemoresistance and immune surveillance 7–10 . Tumour‐derived exosomes have a critical role in the tumour environment through short‐ and long‐distance delivery of biological molecules 10–13 . Increasing evidence has shown that exosomes derived from tumour cells affect the proliferation and metastasis of recipient tumour cells 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…In exosomes, encapsulating various biomolecules, including lipids, proteins, coding and non‐coding RNAs, and DNA species, promotes the survival and dissemination of cancer cells against stress, chemoresistance and immune surveillance 7–10 . Tumour‐derived exosomes have a critical role in the tumour environment through short‐ and long‐distance delivery of biological molecules 10–13 . Increasing evidence has shown that exosomes derived from tumour cells affect the proliferation and metastasis of recipient tumour cells 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate (within 5 years) of CRC is still only about 50%. this low survival rate of CRC is highly related to its chemotherapy resistance (Ma et al 2023). Therefore, elucidating the mechanism of chemoresistance in CRC is a hot research topic at home and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…5-FU-based adjuvant chemotherapy is recommended for all eligible patients with stage III colon cancer after radical resection, as well as high-risk stage II colon cancer patients (poorly differentiated, T4 tumors, tumor perforation and less than 12 lymph nodes retrieved) [ 4 ]. However, the efficacy of chemotherapy in CRC remains suboptimal, and most CRC patients ultimately develop drug resistance [ 5 ]. In addition, more than 90% of patients diagnosed with metastatic CRC would suffer chemotherapy failure due to drug resistance, and their 5-year survival rate is only 14% [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of chemotherapy in CRC remains suboptimal, and most CRC patients ultimately develop drug resistance [ 5 ]. In addition, more than 90% of patients diagnosed with metastatic CRC would suffer chemotherapy failure due to drug resistance, and their 5-year survival rate is only 14% [ 5 , 6 ]. Therefore, elucidating the mechanism of resistance of CRC to 5-FU is of great significance in designing successful chemotherapy regimens and improving the prognosis of patients with CRC.…”
Section: Introductionmentioning
confidence: 99%